An Unusual Presentation of Pelvic Leiomyomatosis Misdiagnosed as Disseminated Malignancy. (11th November 2012) - Marwah, Nisha; Duhan, Amrita; Aggarwal, Garima; Sen, Rajeev
Abstract : Leiomyomatosis peritonealis disseminata (LPD) is an exceedingly rare, usually benign condition that clinically simulates a disseminated malignancy, occurring predominantly in women of childbearing age. We present a case of LPD in a postmenopausal woman who had undergone hysterectomy 8 years back for fibroids along with simultaneous presence of pelvic metastasis from breast carcinoma.